2013
DOI: 10.1177/0272431613510404
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescent Perceptions of Neighborhood

Abstract: Considerable evidence shows the detriments of neighborhood social disorganization for urban youth. Researchers have focused less on potential neighborhood strengths or on the interplay of neighborhood perceptions and objective neighborhood characteristics. The authors examined the presence and perception of positive and negative neighborhood characteristics among urban ethnically diverse families, the similarity in early adolescents’ and mothers’ perceptions, and the association between sociodemographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Residing in neighborhoods with higher proportions of more educated residents is associated with greater academic achievement (Ainsworth, 2002) and higher academic aspirations (Plunkett, Abarca-Mortensen, Behnke, & Sands, 2007). Also, youth who live in high resourced neighborhoods report higher grades than their counterparts (Byrd & Chavous, 2009) and youth who report greater neighborhood disadvantage and problems report lower grades than their counterparts (Witherspoon & Hughes, 2014). …”
Section: Neighborhoods and Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Residing in neighborhoods with higher proportions of more educated residents is associated with greater academic achievement (Ainsworth, 2002) and higher academic aspirations (Plunkett, Abarca-Mortensen, Behnke, & Sands, 2007). Also, youth who live in high resourced neighborhoods report higher grades than their counterparts (Byrd & Chavous, 2009) and youth who report greater neighborhood disadvantage and problems report lower grades than their counterparts (Witherspoon & Hughes, 2014). …”
Section: Neighborhoods and Adjustmentmentioning
confidence: 99%
“…There has been a growing interest in understanding the multiple contexts in which youth, particularly youth of color (Garcia Coll et al, 1996), are embedded and how these contexts singularly and interactively influence development (Burton, Price-Spratlen, & Beale-Spencer, 1997; Furstenberg, Cook, Eccles, & Elder, 1999; Witherspoon & Hughes, 2014). Among these important contexts are youths’ residential neighborhoods.…”
mentioning
confidence: 99%
“…Elements that promoted safety include protective social ties, social control, and the sense of one's ability to avoid danger, while perceived danger was associated with violence, being previously victimized, and the absence of social control (Zuberi, 2018). This dual reality of safety and danger may be attributed to perceptions of both positive and negative features of neighborhoods, reflecting the pluralism of neighborhood life (Witherspoon & Hughes, 2014).…”
Section: Perceptions Of Safetymentioning
confidence: 99%
“…Components of the neighborhood environment such as neighborhood disorder could serve as targets for the development of multilevel or other intervention strategies aimed at reducing depression, particularly in areas that are structurally disadvantaged. Living in disadvantaged areas has been found to be linked with a variety of other poor health outcomes, particularly for adolescents (Witherspoon & Hughes, 2014). Therefore, if perceived neighborhood disorder can moderate that association, it may be a possible target for intervention.…”
mentioning
confidence: 99%
“…Neighborhood disorder is a practical and feasible option as a target for structural interventions and should be considered. Interventions aimed at decreasing neighborhood disorder for mental health have been found to be promising (Casciano & Massey, 2012;Leventhal & Brooks-Gunn, 2003;Witherspoon & Hughes, 2014). A randomized-controlled trial aimed at changing the neighborhood structural environment of participants was found to decrease neighborhood disorder, resulting in an overall reduction in depressive and distress/anxiety symptoms (Leventhal & Brooks-Gunn, 2003).…”
mentioning
confidence: 99%